2017
DOI: 10.4236/jbm.2017.53013
|View full text |Cite
|
Sign up to set email alerts
|

Qi Gong and Heart Rate Variability: A Systematic Review

Abstract: Qì Gōng is a type of exercise that involves meditation and is used for health. With a background from the martial arts, it is known also as an auto healing exercise with three main elements according to Traditional Chinese Medicine (TCM): body focus (posture and movement), breathing and mind focus (meditative elements). Heart rate variability is a tool that allows us to measure the autonomic system velocity to detect and respond to unexpected stimuli. So our goal was to build a systematic review of Qi Gong and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
(19 reference statements)
1
3
0
Order By: Relevance
“…Frequency domain analysis parameters of HRV like LFnu, HFnu and LF/HF are considered to be representative of the autonomic tone. The practice of various types of meditation has consistently shown to increase the parasympathetic tone (increase in HFnu) and reduce the sympathetic tone (LFnu and LF/HF) for the duration of meditation 7, 11. The analysis of HRV data for these parameters in present study revealed that LFnu and LF/HF decreased whereas HFnu increased during cleaning and meditation, compared to their baseline values, thereby indicating that parasympathetic dominance operated during both these procedures.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Frequency domain analysis parameters of HRV like LFnu, HFnu and LF/HF are considered to be representative of the autonomic tone. The practice of various types of meditation has consistently shown to increase the parasympathetic tone (increase in HFnu) and reduce the sympathetic tone (LFnu and LF/HF) for the duration of meditation 7, 11. The analysis of HRV data for these parameters in present study revealed that LFnu and LF/HF decreased whereas HFnu increased during cleaning and meditation, compared to their baseline values, thereby indicating that parasympathetic dominance operated during both these procedures.…”
Section: Discussionsupporting
confidence: 49%
“…In such studies, one of the frequently used variable has been heart rate variability (HRV), a psycho-physiological parameter which is robust marker of mortality and cardiovascular health. Several studies have clearly shown the salutary effects of meditation on HRV 7, 8, 9, 10, 11. However, Heartfulness practices and their effect on cardiovascular measures has not been studied yet.…”
Section: Introductionmentioning
confidence: 99%
“…Practicing Tai Chi and Qigong may reduce the sympathetic nerve tension, increase the parasympathetic nerve tension, and improve the peripheral autonomic nerve activity. 68 , 69 In addition, the training content of alternative exercise traditions is simple and requires minimal equipment and venues. In the context of the COVID-19 pandemic, these forms of exercise are safer and more natural than other sports activities.…”
Section: Discussionmentioning
confidence: 99%
“…The power of martial arts as a mind-body practice and discipline potentially lies in their ability to foster optimal sympathovagal balance that affords flexible and optimal compassionate responding. Similar other mind-body practices such as Tai Chi, Qigong and yoga that pair mindful movement with breathing/breath control exercises have been shown to stimulate the parasympathetic nervous system (Ramos et al, 2017;Sullivan et al, 2018;Walther et al, 2018) and many martial forms/kata have sections that are deliberately practiced in a slow, controlled and meditative way (Rawcliffe, 2003). Paced rhythmic breathing synchronized with rhythmic muscle contraction activates and produces a more resilient parasympathetic response in the face of stress than either alone (Chin and Kales, 2019), both of which are integral to martial arts practice and are often seen in prearranged practice drills (i.e., Kihon), all conducted with respect for oneself and one's partner.…”
Section: Radically Embodied Compassion As Understood Cultivated and mentioning
confidence: 99%